Impact of chronic doxycycline treatment in the APP/PS1 mouse model of Alzheimer's disease. (15th May 2022) - Gomez-Murcia, Victoria; Carvalho, Kevin; Thiroux, Bryan; Caillierez, Raphaëlle; Besegher, Melanie; Sergeant, Nicolas; Buée, Luc; Faivre, Emile; Blum, David
Abstract: Due to the pathophysiological complexity of Alzheimer's disease, multitarget approaches able to mitigate several pathogenic mechanisms are of interest. Previous studies have pointed to the neuroprotective potential of Doxycycline (Dox), a safe and inexpensive second-generation tetracycline. Dox has been particularly reported to slow down aggregation of misfolded proteins but also to mitigate neuroinflammatory processes. Here, we have evaluated the pre-clinical potential of Dox in the APP/PS1 mouse model of amyloidogenesis. Dox was provided to APP/PS1 mice from the age of 8 months, when animals already exhibit amyloid pathology and memory deficits. Spatial memory was then evaluated from 9 to 10 months of age. Our data demonstrated that Dox moderately improved the spatial memory of APP/PS1 mice without exerting major effect on amyloid lesions. While Dox did not alleviate overall glial reactivity, we could evidence that it rather enhanced the amyloid-dependent upregulation of several neuroinflammatory markers such as CCL3 and CCL4. Finally, Dox exerted differentially regulated the levels of synaptic proteins in the hippocampus and the cortex of APP/PS1 mice. Overall, these observations support that chronic Dox delivery does not provide major pathophysiological improvements in the APP/PS1 mouse model. Highlights: Chronic treatment of APP/PS1 with Doxycycline mice moderately improves memory. Doxycycline mice does not reduce amyloid load of APP/PS1 mice. Doxycycline mice does not reduce neuroinflammation in the hippocampus and cortex of APP/PS1 mice. Doxycycline enhances the level of synaptic proteins in the hippocampus but not in the cortex.